2017
DOI: 10.21608/alexja.2017.5763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enriched Gluten Free Biscuits with Chickpea Flour or Kareish Cheese on Chemical, Nutritional Value, Physical and Sensory Properties

Abstract: The purpose of this research was to investigat the effect of substitutions chickpea flour or kareish cheese with rice flour at different levels (0, 2.5,5, 7.5, 10 and 12.5%) on chemical composition, nutritional evaluation, physical and sensory properties of gluten free sweet or salty biscuits. The results showed that as a result of increasing the levels of substitutions of chickpea flour or kareish cheese, the moisture, protein, ash and fat were increased. However carbohydrates contents were decreased compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…However, the carbohydrate content was reduced compared to other control biscuits. Thus, the nutritional value of sweet cookies was increased compared to control samples [40]. According to some scientists, biscuits with higher protein content showed higher acceptability than biscuits with higher starch content and no added protein [41].…”
Section: Tablementioning
confidence: 98%
“…However, the carbohydrate content was reduced compared to other control biscuits. Thus, the nutritional value of sweet cookies was increased compared to control samples [40]. According to some scientists, biscuits with higher protein content showed higher acceptability than biscuits with higher starch content and no added protein [41].…”
Section: Tablementioning
confidence: 98%
“…Specifically, chickpeas (Cicer arietinum L.) are notable for their high protein content and are valued for their excellent balance of essential amino acids, substantial levels of complex carbohydrates (resulting in a low glycemic index), antioxidant compounds such as polyphenols, vitamins, and minerals. Moreover, they contain relatively low levels of anti-nutritional factors [9]. Consequently, incorporating chickpea flour into bakery products could enhance the bioactive profile of new items.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, incorporating chickpea flour into bakery products could enhance the bioactive profile of new items. El-Gohery [9] found that substituting wheat and barley pretzels with 40% chickpea or 20% sweet lupine powder increased their total phenolic and total flavonoid contents while preserving or enhancing their sensory characteristics. However, it is crucial to note that processing can impact the polyphenol profile, consequently affecting the antioxidant properties and nutritional value of the reformulated food [10].…”
Section: Introductionmentioning
confidence: 99%